Development of a phage-based diagnostic sensor for active Tuberculosis - Zhao, Ning, author; Fisk, John D., advisor; Spencer, John S., committee member; Henry, Charles S., committee member; Peebles, Christie, committee member (Colorado State University. Libraries, 2016)
Antibodies, the quintessential biological recognition molecules, are not ideal for many applications because of their large size, complex modifications, and thermal and chemical instability. Identifying alternative scaffolds that can be evolved into tight, specific binding molecules with improved physical properties is of increasing interest, particularly for biomedical applications in resource-limited environments. Hyperthermophilic organisms, such as Sulfolobus solfataricus, are an attractive source of highly stable proteins as starting points for alternative molecular recognition scaffolds. We describe the first application of phage display to identify binding proteins based on the Sulfolobus solfataricus protein Sso7d scaffold. Sso7d is a small (approximately 7 kDa, 63 amino acids), cysteine free DNA-binding protein with a melting temperature of nearly 100 °C. Tight binding Sso7d variants were selected for a diverse set of protein targets from a 1010 member library, demonstrating the versatility of the scaffold. These Sso7d variants are able to discriminate among closely-related human, bovine, and rabbit serum albumins. Equilibrium dissociation constants in the nanomolar to low micromolar range were measured via competitive ELISA. Importantly, the Sso7d variants continue to bind their targets in the absence of the phage context. Furthermore, phage-displayed Sso7d variants retain their binding affinity after exposure to temperatures up to 70 °C. Taken together, our results suggest that the Sso7d scaffold will be a complementary addition to the range of non-antibody scaffold proteins that can be utilized in phage display. Variants of hyperthermostable binding proteins have potential applications in diagnostics and therapeutics for environments with extreme conditions of storage and deployment. One application for utilizing Sso7d evolved binding molecules is development of Tuberculosis (TB) diagnostic tests. TB is the leading cause of death from infectious disease worldwide. The low sensitivity, extended processing time and high expense of diagnostics are major challenges to the detection and treatment of TB. Mycobacterium tuberculosis ornithine transcarbamylase (Mtb OTC, Rv1656) has been identified in the urine of patients with active TB infection, making Mtb OTC a promising target for point-of-care diagnostics in resource-limited settings. We are motivated to engineer phage-based diagnostic systems that feature improved physical stability, cost of production and sensitivity relative to traditional antibody-based reagents. Specific binding proteins with low nanomolar affinities for Mtb OTC were selected from the naïve Sso7d phage library. Phage particles displaying Sso7d variants along with a monoclonal antibody (mAb) generated by hybridoma technology were utilized to generate a capture ELISA-based assay for Mtb OTC. The ELISA assay signal is linear over the target concentration range of 2.0-125.0 ng/mL with limit of detection 0.4 ng/mL (12 pM), which is comparable to commercial available antibody-based assays. Importantly, this assay maintains functionality at both neutral and basic pH in presence of salt and urea over the range of concentrations typical for human urine. Furthermore, towards our phage-based diagnostic test development goal, a test with a pair of phage displaying 2 different Sso7d variants was established with a limit of detection 4.5 ng/mL (130 pM). Stability of TB diagnostic test is improved at acidic conditions in presence of salt and urea in the typical concentration range of human urine, which may due to the replacement of mAb with phage particles. This result demonstrates that phage particles replacing antibodies in the diagnostic test has the potential to improve stability at harsh conditions.
Keywords: diagnostic test; phage display; tuberculosis; molecular recognition; alternative scaffold; thermostable protein